O conteúdo retórico do direito à privacidade e a validade da prova mediante filmagens nos ambientes público e privado - Freire Júnior, Américo Bedê (2014)
The thesis is focused on the following problem: which would be the criterion for the validation of the proof obtained by the camera filming, in the speech of the judiciary, considering the characteristics of the society of spectacle, risk and consumption we live in, in which the State and its citizens are constantly filming all individuals? The issue is analyzed through a rhetoric perspective and, therefore, seeks to establish some topoi that allow its examination. The thesis seeks to justify that video evidence is generally admitted for criminal prosecution in a court of law. In civil cases its admittance depends on the analysis of the situation presented. Finally, in labor matters, the use of video evidence is prohibited as a general rule, excepted only when related to issues of safety. Intimacy, in our time, must be compatible with other fundamental rights, fulfilling a necessary social role. In this context, any video evidence can only be validated, in a court of law, if motivated by a higher interest. For the disclosure of any footage, the control of the motive is the key to determine the scope of the right to privacy. That content cannot be defined in advance and the rhetorical control of the arguments is what will make possible to expand the fundamental rights. The legitimation of the reasons why the video was made should also be imposed to the judge, who must base his decision with consistency, analyzing all the arguments in favor and against the admittance of the footage as an evidence. The biggest concern is deciding what is the best criterion to justify the validity of the proof. The definition of this criterion must be based on topical logic, starting from the problem. In other words, it is the case that reduces the complexity of the affair and, at the same time, reveals what is the best hermeneutical solution to preserve the right to privacy or to preserve any fundamental rights in collision. We must accept the technological evolution, but it is essential that there must be a compatibility between these advances and the respect to the fundamental right of privacy.